1984
DOI: 10.1128/aem.48.5.1020-1025.1984
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 4-Chlorobenzoic Acid by Arthrobacter sp

Abstract: A mixed population, enriched and established in a defined medium, from a sewage sludge inoculum was capable of complete mineralization of 4-chlorobenzoate. An organism, identified as Arthrobacter sp., was isolated from the consortium and shown to be capable of utilizing 4-chlorobenzoate as the sole carbon and energy source in pure culture. This organism (strain TM-1), dehalogenated 4-chlorobenzoate as the initial step in the degradative pathway. The product, 4-hydroxybenzoate, was further metabolized via proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…Arthrobacter sp. strain TM-1 was able to dehalogenate 4-chloro-, 4-bromo-and 4-fluorobenzoate, but only 4-chlorobenzoate supported growth [230]. The dehalogenase of the Pseudomonas sp.…”
Section: Aerobic Degradation Of Halobenzoatesmentioning
confidence: 99%
“…Arthrobacter sp. strain TM-1 was able to dehalogenate 4-chloro-, 4-bromo-and 4-fluorobenzoate, but only 4-chlorobenzoate supported growth [230]. The dehalogenase of the Pseudomonas sp.…”
Section: Aerobic Degradation Of Halobenzoatesmentioning
confidence: 99%
“…TM-I (MARKS et al 1984b), it was shown that the novel hydroxyl group was derived from water. 4-hydroxybenzoate was subsequently hydroxylated to 3,4-dihydroxybenzoate (KLA- GES and LINGENS 1979, MARKS et al 1984a, RUISINGER et al 1976, VAN DEN TWEEL et al 1986) and cleaved either by the orrho pathway to cis,&-muconic acid (KLAGES and LINGENS , RUISINGER et al 1976 or by the meta pathway to 2-hydroxy-4carboxymuconic acid semialdehyde ( KLAGES and LINGENS 1979).…”
Section: Hydroxylationdechlorinationmentioning
confidence: 99%
“…[126]: even the anaerobic degradation of guanine involves two separate sets of three hydrolases each [132]. Furthermore, reports of hydrolytic dechlorinations at an aromatic ring are still rare [133,134] compared with occasional oxidative dehalogenation and the more frequent dehalogenation subsequent to ring cleavage [135], and with the reductire reactions [77,136]. The hydrolytic reactions at the aromatic s-triazine ring are facilitated by the incomplete delocalisation of the ~r-electrons [112], which results in a low electron density at the carbon atoms and susceptibility to nucleophilic attack.…”
Section: Summing Upmentioning
confidence: 99%